Carbon Critical Masterplanning tool - Prokofiev, Elias (2014)
With the climate change issues growing in importance on the social agenda, the field of urban masterplanning is of no exception when it comes to minimizing the carbon footprint in a variety of projects. The aim of this thesis has been to prepare the Carbon Critical Masterplanning tool, a software plugin for carbon dioxide emissions assessment developed by Atkins, to be used in Swedish conditions. The main targets were to improve the areas of the tool associated with energy conversion and renewable energy sources, and to test the tool in a real case.